2011
DOI: 10.1074/jbc.m110.170761
|View full text |Cite
|
Sign up to set email alerts
|

Linked Thioredoxin-Glutathione Systems in Platyhelminth Parasites

Abstract: In most organisms, thioredoxin (Trx) and/or glutathione (GSH) systems are essential for redox homeostasis and deoxyribonucleotide synthesis. Platyhelminth parasites have a unique and simplified thiol-based redox system, in which the selenoprotein thioredoxin-glutathione reductase (TGR), a fusion of a glutaredoxin (Grx) domain to canonical thioredoxin reductase domains, is the sole enzyme supplying electrons to oxidized glutathione (GSSG) and Trx. This enzyme has recently been validated as a key drug target for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Recently, a mechanism for the Grx glutathionylation activity of TGR from Echinococcus granulosus (EgTGR) has been suggested by Bonilla et al (55). They showed that the Grx glutathionylation activity of EgTGR requires the Grx domain as well as the selenocysteine residue.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a mechanism for the Grx glutathionylation activity of TGR from Echinococcus granulosus (EgTGR) has been suggested by Bonilla et al (55). They showed that the Grx glutathionylation activity of EgTGR requires the Grx domain as well as the selenocysteine residue.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that in schistosomes Trx would only reduce GSSG under extreme oxidative stress; therefore, it is not clear whether reduction of GSSG catalyzed by Trx-1 is physiologically relevant in S mansoni . In contrast, in Echinococcus granulosus , a tapeworm parasite with a redox network similar to that found in schistosomes [165], it has been shown that that Trx is able to reduce GSSG and to catalyze deglutathionylation reactions at high concentrations of GSSG in which the activity of its TGR would be inhibited [166]. These results suggest that redox pathways may vary in different Platyhelminthes parasites.…”
Section: The Thioredoxin Systemmentioning
confidence: 99%
“…The difference between the deglutathionylation reactions of E. granulosus TGR and S. mansoni TGR may be explained by different distances between cysteines in the Grx active sites of the two proteins. In E. granulosus TGR, the distance between Cys-31 and Cys-34 is longer than that between Cys-28 and Cys-31 in S. mansoni TGR and, therefore, the accessibility of Cys-34 to Cys-31 may be somewhat limited in E. granulosus TGR [166, 175]. …”
Section: The Thioredoxin Systemmentioning
confidence: 99%
“…Recently, a mechanism for the Grx deglutathionylation activity of TGR from Echinococcus granulosus (EgTGR) has been suggested [67]. It was shown that the Grx activity of EgTGR requires the Grx domain and the selenocysteine residue.…”
Section: Functions and Properties Of Tgr Enzymesmentioning
confidence: 99%